An investigation of the economics of using welded layers for some parts of worm presses for the extraction of oil from sunflower seeds - Marušić, Vlatko (Materiali in tehnologije, 2009)
The working parts of worm presses from different manufacturers were collected from oil mills in Croatia, Vojvodina and Bosnia and Herzegovina. The chemical composition, microstructure and hardness were determined, and the wear was examined for the original (imported) and the substituted (domestic) parts. The direct costs of tribological origin are larger for the substitute parts than for the original parts and they depend on the protective surface layer. The indirect tribological losses are a few tens of times greater than the direct tribological losses. The wear resistance of the welded layers was tested experimentally on extraction cage knives and the results are compared to carburised knives (the substitution solution) commonly used in oil mills. It was found that the wear resistance of the welded layers does not depend only on the surface hardness, but more so on the microhardness and the distribution of the carbide particles in the tough matrix. Based on recordings in oil mills and on the results of our investigation, we concluded that the use of welded layers instead of carburised layers could extend the life cycle of the parts of the presses. In this way, the efficiency of the oil extraction could be increased and the economics of operating oil mills could be improved.
Keywords: stiskalnice; zvari; mikrostruktura; obraba